Popular tools for malware data analysis - Liu, Jinliang (2016)
With the arising of smartphone usage, especially for Android OS, users are relying on their mobile devices increasingly. However, Android Malware brings significant threats to the eco-system. In this project, several effective Malware detection tools are implemented and afterwards evaluated on their accuracy and efficiency. Also, several commonly used classifiers are implemented and their performances are compared in classifying Android Malware. Additionally, concept drift in Android Malware is studied and evaluated on certain Malware datasets.